Cloud Computing For E-Learning System Based On System Architecture - Muruganandam, S; Sruthi, KLV (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing is growing rapidly, with applications almost in any area, including education. E-Learning system requires many hardware and software resources. Therefore, there is a need to redesign the educational system to meet the needs better. The advent of computers with sophisticated software has made it possible to solve many complex problems very fast and at a lower cost. This paper introduces the characteristics of the current E-Learning and then analyses the concept of cloud computing and describes the architecture of cloud computing platform by combining the features of E-Learning. This paper describes the following aspects: architecture, construction method and external interface with the model and tried introduce cloud computing to E-Learning. Architecture